Eyeliner Fabrication from Coconut Shell Waste (Cocos Nucifera) with Xanthan Gum Binder (C35H49O29) - Tamara Rizky Senda; Upik Nurbaiti; Fianti; Budi Astuti; Agus Yulianto (Universitas Negeri Semarang, 2025)
Eyeliner is a decorative cosmetic or make-up product. Eyeliner functions to help emphasize and make the shape of the eyes more prominent and more expressive, make makeup more dramatic without doing many steps, and cover the false eyelash line that sticks to the eyes. This study aims to determine whether activated carbon from coconut shell waste can be used as a natural dye in eyeliner fabrication. This research uses a laboratory experiment method, namely by mixing materials consisting of distilled water, xanthan gum, tween 80, propylene glycol, methylparaben, CH_3 COOH solution with distilled water, ethanol, and carbon pigments in it. Xanthan gum and carbon are mixed in a ratio of 1:10; 1:12; 1:14; 1:16; 1:8; and 1:20 until homogeneous. Fabrication properties were tested, namely homogeneity, pH, drying time, and color tests on eyeliner fabrication. the results were analyzed descriptively. Based on the results obtained, the six fabricated formulations have a deep black color and have an average particle size of 8.1 µm, have an average pH of 6.3, an average drying time of 303 seconds, the six formulations have an evil Minister color, After Dark, Deep Forest chocolate, Holy Crow, Smoked black coffee, Indigo brown ink. It was concluded that pigments from coconut shell carbon can be used as natural dyes in eyeliner fabrication. However, in the physical properties test, namely the homogeneity test and dry time test for eyeliner fabrication, there are still discrepancies in the literature.